Evaluating the impact of type 2 diabetes mellitus on pulmonary vascular function and the development of pulmonary fibrosis - Mzimela, Nhlakanipho; Dimba, Nosipho; Sosibo, Aubrey; Khathi, Andile (Frontiers in Endocrinology, 2024)
The increasing prevalence of type 2 diabetes mellitus (T2DM) is a significant worldwide health concern caused by sedentary lifestyles and unhealthy diets. Beyond glycemic control, T2DM impacts multiple organ systems, leading to various complications. While traditionally associated with cardiovascular and microvascular complications, emerging evidence indicates significant effects on pulmonary health.Pulmonary vascular dysfunction and fibrosis, characterized by alterations in vascular tone and excessive extracellular matrix deposition, are increasingly recognized in individuals with T2DM. The onset of T2DM is often preceded by prediabetes, an intermediate hyperglycemic state that is associated with increased diabetes and cardiovascular disease risk. This review explores the relationship between T2DM, pulmonary vascular dysfunction and pulmonary fibrosis, with a focus on potential links with prediabetes. Pulmonary vascular function, including the roles of nitric oxide (NO), prostacyclin (PGI2), endothelin-1 (ET-1), thromboxane A2 (TxA2) and thrombospondin-1 (THBS1), is discussed in the context of T2DM and prediabetes. Mechanisms linking T2DM to pulmonary fibrosis, such as oxidative stress, dysregulated fibrotic signaling, and chronic inflammation, are explained. The impact of prediabetes on pulmonary health, including endothelial dysfunction, oxidative stress, and dysregulated vasoactive mediators, is highlighted.Early detection and intervention during the prediabetic stage may reduce respiratory complications associated with T2DM, emphasizing the importance of management strategies targeting blood glucose regulation and vascular health. More research that looks into the mechanisms underlying pulmonary complications in T2DM and prediabetes is needed.